Development of The Ensiklopedia Tumbuhan Flipbook as a Science Learning Resource in Elementary School: Pengembangan Flipbook “Ensiklopedia Tumbuhan” Sebagai Sumber Belajar Sains di Sekolah Dasar - Fitriana Dwi Setyaningrum; Dewi Masithoh (IAIN Sorong, 2025)
The development of science and technology has accelerated, so education needs new technology. Teachers are limited in their use of digital science learning media in elementary schools. Books are not being used as full science learning resources, so new learning media are needed. This study aims to develop a flipbook called